(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2024)
The fundamental rights, freedoms and legitimate interests of a person, being subject to the greatest restrictions during criminal proceedings, are guaranteed by the existence of substantive and procedural rules in the legislation aimed at protecting, defending and implementing procedural guarantees of participants in criminal proceedings. The dynamics of social, political, economic and legal life, the social mentality of today, as well as convergence processes determine the adaptation of national criminal procedure legislation to International law. However, the issues of adaptation of national legislation to the provisions of foreign legislation in terms of guaranteeing each participant in criminal proceedings the protection, defence and realisation of their rights, freedoms and legitimate interests in accordance with international standards remain controversial. At the same time, there are a number of gaps and inconsistencies in the provisions of the criminal procedure legislation, the gradual elimination of which will allow Ukraine to reach the international level as a state that guarantees each participant in criminal proceedings the protection, defence and exercise of their rights, freedoms and legitimate interests in accordance with European standards, as well as reduce the number of applications to the European Court of Human Rights. Based on the results of the study, and on the basis of a selective analysis of foreign experience of certain countries, the article identifies the existing problematic issues related to the guarantee of the rights of participants to criminal proceedings, and also formulates proposals for improving criminal procedure legislation in this area, using international experience. The problematic areas of guaranteeing the rights of participants to criminal proceedings include the legal status of individual participants to criminal proceedings, compensation for damages, and the use of procedural terminology. In order to improve and bring the criminal procedure legislation of Ukraine closer to international standards in terms of protection, safeguarding and realisation of the rights, freedoms and legitimate interests of participants in criminal proceedings, the following proposals have been presented: to establish a unit, body or organisation for the protection of the rights, freedoms and legitimate interests of witnesses with the development of appropriate programmes for their protection; to introduce the use of separate procedural terminology; to develop a procedure for granting and exercising the right to free legal aid to victims, civilians as well as the procedure for compensation for damage caused by a criminal offence.